(untitled) (Malaysian Journal of Civil Engineering, 2018)
Concrete is one of the most popular and widely used construction materials in the world. Concrete provides suitable features for construction such as durability, fire resistance, satisfactory compressive strength, availability and is economic as well compared to other construction materials. Now a day, depletion of natural resources and disposal of construction & demolition (C & D) waste related problems claim environmental threat. Recycled aggregate sourced from those construction and demolition waste can be a promising solution to replace natural aggregate in concrete production. This paper identifies some of the important features and properties of recycled aggregate (RA) and recycled aggregate concrete (RAC) from an engineering point of view. Some unsolved issues like limiting the values for characterization of recycled aggregate, stress-strain relations, lack of development of code provisions are also addressed in this paper. Moreover, brief features of a numerical study in RAC are described. Lastly, several positive and negative aspects of the economics of RAC is emphasized. In a nutshell, this research paper pointed out the numerous essence of using RAC in concrete engineering.